P064 Adipose tissues obtained from ra and oa patients differ in cytokine and chemokine secretion. (21st February 2018) - Plebanczyk, M; Radzikowska, A; Burakowski, T; Maslinski, W; Kontny, E
Abstract : Introduction: Rheumatoid arthritis (RA) and osteoarthritis (OA) lead to joint destruction and disability. Although both diseases are characterised by inflammation of the joints as well as systemic inflammation, their pathogenesis is different. Despite the progress in the treatment both diseases are still incurable. Articular adipose tissue (AAT) and subcutaneous adipose tissue (ScAT) are supposed to contribute to joint and systemic inflammation, respectively. Our previous work showed that AAT from RA patients synthesises factors relevant to disease pathogenesis and/or progression and this secretion is usually higher from articular than subcutaneous adipose tissue. 1, 2 Objectives: The aims of present work were (i) to investigate whether AAT obtained from OA patients is also more active than ScAT and (ii) to compare secretory activity of adipose tissues from RA and OA patients. Methods: AAT and ScAT explants obtained from OA [(n=44; female (F)/male (M)=36/8; age=62 (mean) (35–71) (min-max)] and RA (n=43; F/M=35/8; age=54 (31–70)] patients during knee joint replacement surgery were cultured (100 mg/ml) for 24 hours in DMEM. Concentrations of proinflammatory (IL-6, TNF), anti-inflammatory (IL-1Ra, IL-10, TGFβ) cytokines, chemokines (CCL2, CCL5) and metalloproteinase MMP-3 was measured in culture supernatants by ELISA. Results: In both diseases AAT secreted spontaneously more IL-1Ra, TGFβ and MMP-3 than ScAT while the release of other factors was minute (TNF, IL-10, CCL5) or moderate (CCL2) and did not differ between tissues. The only exception was IL-6 produced in larger quantity by AAT than ScAT from OA patients. Both adipose tissues from OA patients released significantly more TNF, IL-1Ra and CCL2 than tissues from RA patients. Moreover, AAT from OA produced more MMP-3 than respective tissue of RA patients while rheumatoid ScAT secreted more TGFβ. We did not find differences in basal secretion of IL-6, IL-10 and CCL5 between diseases. Conclusions: Despite the fact, that similarly to RA the secretion of cytokines and chemokines in OA was usually higher in AAT than in ScAT, also the latter tissue released considerable quantity of tested factors and thus may contribute to systemic inflammation. Unexpectedly, our results give also evidence that basal secretory activity of adipose tissues from OA patients is usually higher than from RA patients. It is possibly caused by different anti-inflammatory treatment, stronger in RA than OA patients, with resulting poor control of inflammation in OA. References: . Kontny E, et al. Ann Rheum Dis2012;71(2):262–267. . Kontny E, et al. Rheumatology2013;52:2158–2167. Acknowledgements: This work was funded by the National Science Centre (grant number 2012/N/NZ5/00074). Disclosure of interest: None declared